DESAIN MANAJEMEN JARINGAN DENGAN MENGGUNAKAN METODE ROUTING OSPF OTENTIKASI STUDI KASUS PADA SEKOLAH THERESIANA (Information Technology and Telematics, 2013)
Design of network management is one way to manage the network from topology, routing protocols, to any device that will be used in building a network. The existence of a network simulator software can make it easier to design a network that will be made before it is implemented immediately. For implementation in network simulation in this study will use the Packet Tracer software that can run on Windows or Linux operating system. Routing protocol in use Theresiana schools that have not resulted in a maximum flow of data transmission is often impaired, so the need for optimization for network management. Routing protocol that will be implemented at the school Theresiana using OSPF dynamic route, namely by adding commands to securing OSPF Authentication is used. The method used in this study there are 2 of data collection and data sources. The results obtained after using the OSPF routing protocol authentication is network security in schools Theresiana be more secure because it can prevent the addition of the outside procedure. That's why this study uses the underlying routing protocol OSPF Authentication particularly with the addition of features. Keywords: Design of Network Management, Packet Tracer Simulator, OSPF Authentication